Crossmodal Nonspatial Repetition Inhibition Due to Modality Shift. (February 2021) - Zhang, Ming; Wu, Xiaogang; Wang, Aijun
Previous studies have found that processing of a second stimulus is slower when the modality of the first stimulus differs, which is termed the modality shift effect. Moreover, people tend to respond more slowly to the second stimulus when the two stimuli are similar in the semantic dimension, which is termed the nonspatial repetition inhibition effect. This study aimed to explore the modality shift effect on nonspatial repetition inhibition and whether such modulation was influenced by different temporal intervals. A cue–target paradigm was adopted in which modality priming and identity priming were manipulated at three interstimuli intervals. The results showed that the response times under the modality shift condition were slower than those under the modality repeat condition. In trials with modality shift, responses to congruent cues and targets were slower than to incongruent cue–target combinations, indicating crossmodal nonspatial repetition inhibition. The crossmodal nonspatial repetition inhibition effect decreased with increasing interstimuli interval. These results provide evidence that the additional intervening event proposed in previous studies is not necessary for the occurrence of crossmodal nonspatial repetition inhibition.